Validated HPLC Methodology for Pregabalin Quantification in Human Urine Using 1-Fluoro-2,4-dinitrobenzene Derivatization - Mohamedsaid mostafa Said Mostafa; Hosam Abdel Fattah Mohamed Elshebiny; Olfat Elsayed Mostafa; Shimaa Talaat Elsayed; Mohamed Abdelizm Abdelaziz (Drug Analytical Research)
Pregabalin (PGB) is a synthetic drug used for the treatment of central nervous system disorders and neuropathic pain. PGB is metabolized to N-Methyl pregabalin while the rest is excreted virtually unchanged in the urine. Numerous analytical techniques for measuring pregabalin have been documented. This study aimed to validate a simple, sensitive, and accurate method for PGB quantification in human urine using the HPLC technique with 1-Fluoro-2, 4-dinitrobenzene used as a derivatizing agent. One hundred and twenty urine samples were analyzed by a reversed-phase (C18) column and a mixture of acetonitrile and 50 mM KH2PO4 (pH 2.5) (60:40, v/v) as mobile phase and the flow rate was 1 ml/min and the UV detector wavelength was set to 360nm. The procedure was linear within the 10-1000 μg/ml range of PGB in urine (r > 0.99). Intraday and interday RSD precision values fell between 2.8% and 5.9%. 2.5 and 1.5 μg/ml, respectively, were determined to be the method's limits of quantification and detection. The recovery (90.8%) and statistical characteristics show that the suggested method has excellent accuracy and precision. The method is accurate, precise, reproducible, and specific, and it can be applied to regular examinations of pregabalin in urine samples.